ARCO 05 : contemporary art ARCO special A retrospective. - Barro, David; Acuña Garcia, Clara; Allen, Jennifer; Azpiri, Ander; Badia Villaseca, Sara; Benitez, Issa Maria; Berzal, Pablo; Botella Diez del Corral, Ana; Citoler, Pilar; Diaz, Eva; Dietz, Steve; Díaz Guardiola, Javier; et al. (Madrid : ARCO - Feria Internacional de Arte Contemporaneo Madrid, 2005)
Afonso, Albano ; Alejo, Mauricio ; Andersen, Signe Marie ; Apfelbaum, Polly ; Appelt, Dieter ; Artigas, Gustavo ; Ballester, José Manuel ; Barclay, Per ; Barry, Orla ; Benz, Christina ; Blake, Jeremy ; Blanco, Miguel Angel ; Bonillas, Iñaki ; Bonin, Cosima von ; Brambilla, Marco ; Brandl, Herbert ; Bulloch, Angela ; Caivano, Ernesto ; Carter, Nathan ; Castellano, Jacobo ; Catunda, Leda ; Changha Hwang ; Cruz, Angela de la ; Curto, Félix ; Dinh Q. Lê ; Dzama, Marcel ; Escobar, Dario ; Espinosa, Mónica ; Fabre, Jan ; Fernández, Claudia ; Garcia, Dora ; Halley, Peter ; Hendrix, Jan ; Hernández, Diango ; Horn, Rebecca ; Huber, Stephan ; Irazu, Pello ; Jaar, Alfredo ; Jakobsen, Steinar ; Kinoshita, Suchan ; Knoebel, Imi ; Koch, Lucia ; Laib, Wolfgang ; Locher, Thomas ; Louro, Joao ; Lundeby, Tor-Magnus ; Macchi, Jorge ; MacDonald, Euan ; Machulina, Diana ; Marcaccio, Fabian ; marcos, angel ; Margalef, Manel ; Martin, Jason ; Moffatt, Tracey ; Mora, Gabriel de la ; Najjar, Michael ; Negro, Alvaro ; Orozco, Gabriel ; Ortega, Damián ; Paik, Nam June ; Palma, Miguel ; Plensa, Jaume ; Ranner, Alexandra ; Rennó, Rosângela ; Rivero, Elena Del ; Rocin, Daniel ; Ruff, Thomas ; Santomé, Diego ; Sasse, Jörg ; Schinwald, Markus ; Serra, Richard ; Soldevilla, Pere ; Stipl, Richard ; Tabarra, Joao ; Téllez, Javier ; Tim Lee ; Vale, João Pedro ; Vallhonrat, Valentin ; Verbis, Daniel G. ; Vietà, Mayte ; Viola, Bill ; West, Franz ; White-Sobieski, Tim ; Wurm, Erwin
ARCO 05, ARCO - Feria Internacional de Arte Contemporaneo, Madrid. 2005-02-09 - 2005-02-14
boek